Inhibition of capsular protein synthesis of pasteurella multocida strain P-1059 - Sthitmatee N. (2014)
A mutant strain, PBA322, was constructed by electroporation of a phagemid containing the coding region of antisense RNA of the ompH gene, encoding 39 kDa capsular protein or OmpH, into the parental strain P-1059 (serovar A:3) of Pasteurella multocida, and the pathogenicity was determined in mice and chickens. Grayish colonies of the mutant, indicating loss of capsule synthesis, were observed under a stereomicroscope using obliquely transmitted light, while iridescent colonies were observed for the parental strain. Moreover, strain PBA322 showed a low amount of OmpH compared with the parental strain on SDS-PAGE. Additionally, the capsule of strain PBA322 was thinner than that of the parental strain according to electron microscopy, correlating to the attenuation against chickens. In conclusion, strain PBA322, the mutant of P. multocida strain P-1059, was completely attenuated for chickens.